The teaching of cross-cultural skills in the english language classroom - Krayeski, Sofía (2010)
The topic chosen which deals with “teaching of cross-cultural skills in the english classroom” is pretty new in our country. The research focuses on the issue of whether the cultural component of the foreign language is being taught in the english classroom or not. In order to obtain this information a survey was conducted to teachers and students of 1st, 2nd and 3rd years of senior high school, in both private and public schools. The teaching of the english cultural component in our classrooms is very important, since language and culture are connected in certain ways, for that reason, it is important to know if it is being taught in the classrooms. Thinking on this, the university has decided to carry out an investigation in order to find out how much of this component students have in their classrooms.